Detection of glibenclamide adulteration in herbal remedies for diabetes mellitus using TLC - Budi, Andre; Razoki, Razoki; Harahap, Halimah; Amansyah, Adek; Edlin, Edlin; Tarigan, Susiani (Buletin Kedokteran & Kesehatan Prima, 2024)
The widespread use of jamu, a traditional Indonesian herbal medicine, has been accompanied by a surge in adulteration with synthetic drugs to enhance efficacy and sales. This study aimed to detect the presence of glibenclamide, a common adulterant, in antidiabetic jamu product using TLC. This study employed three herbal medicine samples marketed for lowering blood glucose levels, with glibenclamide BPFI serving as a reference standard. Thin-layer chromatography, employing a mobile phase consisting of chloroform, cyclohexane, ethanol, and glacial acetic acid (9:9:1:1), was utilized for the analysis. Thin-layer chromatography (TLC) analysis revealed a standard Rf value of 0.4 for glibenclamide, producing a distinct blue-violet spot when visualized with 10% sulfuric acid. The results indicated that the tested herbal medicine samples did not contain the pharmaceutical substance glibenclamide. This conclusion was drawn from the absence of a corresponding Rf value for glibenclamide in the herbal samples when compared to the reference standard.